Settings determination for numerical transformer differential protection via its detailed mathematical model; IET Generation, Transmission & Distribution; Vol. 14, iss. 10 - Andreev M. V. Mikhail Vladimirovich; Suvorov A. A. Aleksey Aleksandrovich; Ruban N. Yu. Nikolay Yurievich; Ufa R. A. Ruslan Alexandrovich; Gusev A. S. Alexander Sergeevich; Askarov A. B. Alisher Bakhramzhonovich; Kievets A. V. Anton Vladimirovich; Bhalja B. R. Bhavesh (2020, 2020)
Title screen